Knowledge, attitude and practice of prevention towards HIV/AIDS amongst health personnel in Tapah Hospital , Perak, 1996 - Hasnah Bibon; Mohd Hatta Md. Ramli (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
With the increase of HIV/AIDS problem, health personnel are at an increased risk of infection. A cross sectional study was conducted amongst health personnel of Tapah hospital with the objective of determining their. knowledge on HIV/AIDS and their attitudes and practice towards preventive measure. Self-administered questionnaires were used to measure their knowledge, attitudes and preventive measures taken, while observations of their daily work were carried out to determine the practice of 'universal precaution'. There was a total of 222 respondents consisting mainly of Malays (74.8%) and 59.5% of them were females. The mean age of the respondents was 39.5 ± 8.06 and the main duration of service with Ministry of Health was 15.7 ± 9.2. Results showed high level of knowledge amongst respondents (86.9%) and this is statistically significant (p<0.05) according to their place of work where those who work in the ward have high level of knowledge, and also age below 40 years old. It was also found that 73.5% of respondents showed positive attitude towards HIV/AIDS patient and this is significantly related (p<0.05) to their position as medical officers, staff. nurses, hospital assistants and also those with high educational status compared to those in other positions and with primary school education. The practised of universal precaution (theory) was shown by 65.4% of respondents, which was significantly related (p<0.05) to their positions as medical doctors, staff nurses and hospital assistants and also to those who work in the ward compared to those in other positions and other works places. However, a different finding was found based on a 5-day observation of their daily work. During this period, we found 214 incidents of not adhering to tile recommended preventive measure; 67. 5% of which were related to hand washing and wearing of gloves and these unhealthy practices involved most medical officers, staff. nurses and laboratory technologists. So infection control team must actively do supervision to make sure universal precautions are followed for a safe future of health staff: